Pengukuran Kinerja Keuangan Bus Menggunakan Islamicity Performance Index - Mabruroh, Mabruroh; Supriyanto, Trisiladi; Ayyuniyah, Qurroh (ITB AAS INDONESIA Surakarta, 2024)
The development of Islamic banking in Indonesia today has experienced a rapid increase both in quantity and quality. As an institution that operates based on sharia principles, Islamic banks have different characteristics and assessments of financial performance from conventional banks. Islamicity Performance Index is one of the new concepts as a method that can be used to evaluate the performance of Islamic banks which are not only financially but also able to evaluate the principles of fairness and halalness of an Islamic banking.This study aims to reveal the application of sharia principles to the performance of Islamic Commercial Banks in Indonesia for the 2017-2020 period by using the Islamicity Performance Index. The ratios used are Profit Sharing Ratio, Zakat Performance Ratio, Equitable Distribution Ratio, Directors-Employees Welfare Ratio, Islamic Investment Vs Non-Islamic Investment, Islamic Income Vs Non-Islamic Income and the AAOIFI Index. The data used in this research is secondary data. The population of this study is all Islamic Commercial Banks in Indonesia for the 2017-2020 period, with a sample of five banks. Sampling was carried out using purposive sampling method. From the results of this study, it was found that the performance of Islamic banks can be said to be